Organization of adult education in France and Belgium - Орос, І. І. (Scientific notes of the pedagogical department, 2019)
The purpose of the article is to uncover the organization of adult education in France and Belgium.  As for working with the adult population of France, we have highlighted the peculiarities of a new form of organization of continuing vocational education of adults in this country– the educational structure of GRETA. The reason for the emergence in France of such a structure as GRETA was the consequence of general trends in the development of adult education. GRETA's national educational structure in our time is the main organization involved in the continuing vocational education of adults in France. Adult education in France differs significantly from the education of adults in other European countries, because in its organization, the funding plays a significant role in the state, the Ministry of National Education of France and regional education authorities. The leading methodological approach in the process of adult education is the cultural approach, which defines the direction of other approaches - systemic, axiological and activity, that is, traditional as well as non-traditional (hermeneutic, procedural-design) approaches. Adult vocational education is an integral part of the French education system. As a socio-pedagogical phenomenon, adult education is regarded as a factor in socialization and a means to attain a certain level of education, general culture and professional competence, which corresponds to the social and personal needs of adults as subjects of education and work.Belgium consists of 3 language communities – flamanoval, francophone and german-speaking. Against the backdrop of the federal system, the linguistic stratification of the population has problems. The country is fighting the illiteracy of the adult population, resulting in increased literacy of the population. Migration processes are one of the factors leading to the emergence of functional illiteracy in Belgium. The training of functional literacy of adults in Belgium is based on the principles of andragogy. It uses an individual approach and takes into account the internal motivation processes of the learners. Educators who teach adults functional literacy are subject to strict requirements that are defined by the collection of rules and requirements of the "Profile of the teacher of literacy".